Bibliometric Characteristics of Domestic Publications in Gold Open Access Journals: Web of Science, 2008-201 - Markusova Valentina; Zolotova Anna; Mindeli Levan; Ivanov Vladimir (Informaciâ i Innovacii)
The article gives short overview of bibliometric research on Open access journals, its advantages and disadvantages. The bibliometric analysis was based on Russian articles (Research performance-RP) published in the Gold Open Access (OA) journals, indexed in SCI-E (Web of Science) for 2008-2017. Despite the high payment for articles, it was observed a steady increase in the share of Russian publications in Gold OA journals in the total Russian RP: from 7.8% in 2008 up to 13.7% in 2017. This is largely due to active international cooperation with Russian organizations and funding agencies from United States (31%), Germany (29%) and other industrialized countries. Government investment in the Program 5- 100 stimulated a signiﬁcant increase in the share of Gold OA publications by these universities from 21.9% in 2012 to 40.8% in 2017. At the same time period, the share of RAS decreased from 64.8% to 52.9%. Russian scientists use extensively the highest quality foreign journals of the Gold OA system indexed in the SCI-E database, which includes two domestic journals.